Exergetic analysis in a combined gas-steam power cycle with two regenerators in parallel. Issue 2 (15th June 2020) - Caetano, Nattan Roberto; Barreto, Eduardo Xavier; Ruoso, Ana Cristina; Klunk, Marcos Antonio; Wander, Paulo Roberto
This work presents an exergetic analysis applied in a configuration in which two regenerators were in parallel for a combined gas-steam power cycle. The working fluids considered for the gas and vapour cycles were air and water. In this case, two heat recovery steam generators vaporise water and reheat using a steam turbine second stage, where the full power cycle was 10, 000 kW. A numerical study was performed from 100 to 7, 000 kPa steam pressure. The exergy approach was performed in order to maximise the thermal efficiency. The benefits brought by two regenerators was an increase of 37% in the thermal efficiency. Also, the second regenerator reduces the lost exergy in the exhaust gases. Reductions of 81% were observed in the condenser.